KOMUNIKASI PERTEMANAN MELALUI FITUR 'CLOSE FRIENDS' INSTAGRAM PADA MAHASISWA UNIVERSITAS VETERAN BANGUN NUSANTARA SUKOHARJO - Fitriana, Rani; Suryono, Joko (Prodi Ilmu Komunikasi Universitas Sahid Surakarta, 2026)
Friendship Communication Through Instagram's 'Close Friends' Feature Among Communication Science Students Class of 2021 at Universitas Veteran Bangun Nusantara Sukoharjo. Undergraduate Thesis, Communication Science Study Program, Faculty of Social and Legal Sciences, Universitas Veteran Bangun Nusantara Sukoharjo, 2025.The ‘Close Friends’ feature on Instagram allows users to selectively share information with a limited group, enhancing privacy and control over shared content. This study aims to explore and analyze how the Close Friends feature on Instagram influences communication and friendships among university students. The research adopts a qualitative approach, with data collected through in-depth interviews, participatory observation, and content analysis. Data validity is ensured through data triangulation. The results of the study show that the ‘Close Friends’ feature can strengthen mutual trust among friends by allowing users to share more personal and exclusive content. Students feel more comfortable communicating and sharing important moments with their close friends, ultimately strengthening their friendships. In addition, this study also identifies several practical benefits, such as helping students understand the risks and benefits of social media use, and providing insights for social media developers to improve features according to user needs.